The Need To Train Future Teachers In The Use Of Pedagogical Technologies In The Process Of Pedagogical Education - Khudoyberganova Sevinchoy Urazmat kizi (Euro Asian Journal Publishing, 2024)
Some thoughts are expressed on the need to train future teachers to use pedagogical technologies in the process of pedagogical education. The article also presents some thoughts on the pedagogical analysis of the concepts of pedagogical technology, innovative technology and its importance in the educational process.
Keywords: Pedagogical technology; innovative approach; educational process